Physical and biochemical qualities of pressurized and pasteurized longan juices upon storage - Pittaya Chaikham (2018)
The physical and biochemical properties of pressurized longan juice at 500 MPa; 25°C for 30 min and pasteurized juice at 90°C for 2 min were investigated during storage at 4°C for 4 weeks. Color parameters indicated that although enzymatic degradation in pressurized longan juice was the primary cause of lower L parameter (lightness) during storage, its magnitude was apparently lesser than browning caused by Maillard reaction in pasteurized juices reflected by b* (yellowness) and BI (browning index) parameters. The results of residual enzymes showed that during storage, polyphenol-oxidase had greater rate of degradation and was more resistant to pressure than peroxidase. The bioactive components like ascorbic acid in pressurized juice exhibited higher reduction during storage than that of pasteurized juice. However, residual ascorbic acid in pressurized juice was still higher than that thermal treated juice throughout the storage period. The other bioactive components in pressurized juice were also gradually degraded during storage by 71%, 66%, 28% and 37%, while in pasteurized products substantially reduced by 60%, 69%, 23% and 35% for gallic acid, ellagic acid, total phenols and antioxidant activity (DPPH assay), respectively.